2000
DOI: 10.1177/152660280000700310
|View full text |Cite
|
Sign up to set email alerts
|

A Porcine Model of Carotid Artery Thrombosis for Thrombolytic Therapy and Angioplasty: Application of PTFE Graft-Induced Stenosis

Abstract: This carotid artery thrombosis model, which incorporates intimal injury with segmental stenosis, is simple to create and reproducible. It provides not only a model for the evaluation of thrombolytic therapy but also a practical training tool for adjunctive endovascular interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…CT with local contrast agent injection is associated with considerable beam-hardening artifacts as a result of high concentration of contrast agent within the lysis catheter and unnecessary radiation exposure to the operator. Therefore, the increase of patent graft area was examined by angiography, consistent with clinical practice and previous publications (19,35,36). The use of an edge detection program increased the accuracy and reproducibility of the contrast area measurements as opposed to manual segmentation; adjustments were made by the blinded reviewer if necessary.…”
Section: Discussionmentioning
confidence: 89%
“…CT with local contrast agent injection is associated with considerable beam-hardening artifacts as a result of high concentration of contrast agent within the lysis catheter and unnecessary radiation exposure to the operator. Therefore, the increase of patent graft area was examined by angiography, consistent with clinical practice and previous publications (19,35,36). The use of an edge detection program increased the accuracy and reproducibility of the contrast area measurements as opposed to manual segmentation; adjustments were made by the blinded reviewer if necessary.…”
Section: Discussionmentioning
confidence: 89%
“…A full spectrum of procedures in a fully functioning arterial tree can be performed, and realistic endovascular access using a percutaneous or surgical cut-down technique is feasible. Even the lack of natural pathology has also been overcome with artificial induction of both occlusive and aneurysmal disease through iatrogenically injuring vessel endothelium [ 20 ] and suturing constricting prosthetic patches around surgically exposed vessels [ 21 ]. The Porcine Transfer Study [ 22 ] showed significantly improved performance parameters in novices undertaking an iliac stenting procedure after training on a porcine model.…”
Section: Resultsmentioning
confidence: 99%
“…The inner diameter of the artificial vessel in the bioreactor, 4.57 mm, was selected to match the diameter of human coronary arteries 10,28 and the porcine carotid artery, 28,33 which is commonly used for ex vivo scaffolds in tissue engineering. Because porcine carotid arteries have a maximum usable length of approximately 80 mm 38 and approximately 60 mm of flow length after attachment to a bioreactor, the vessel working length was selected to be 60 mm.…”
Section: Experimental Conditionsmentioning
confidence: 99%